(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cloud computing and virtualization are two intertwined technologies that have revolutionized the way computing resources are provisioned, managed, and utilized. Cloud computing provides on-demand access to a shared pool of configurable computing resources, such as servers, storage, and applications, over the internet.